Time management, academic stress, social support and academic performance in sixth-grade primary school students - Pérez-Briones, Nancy Griselda (2025)
Introduction: Time management is important at all educational levels, since poor practice leads to procrastination of school activities, generating academic stress and affecting academic performance. On the other hand, social support has been mentioned that it can be an enhancer of satisfactory performance since it contributes to the coping of stressful situations and to education in the organization of academic activities. Objective: To determine the influence of time management on academic stress, social support and academic performance in sixth grade students. Material and Methods: A descriptive, correlational, predictive, cross-sectional design was carried out. The sample consisted of 70 elementary school students selected by non-probabilistic convenience sampling. The following were used for data collection: Sociodemographic Data Questionnaire, Time Management Behavior Questionnaire (TMBQ)  to measure time management, the System Inventory of Cognitive and Cognitive Systems (SISCO) Academic Stress, and the Family and Friends Social Support Scale (AFA-R). Results: The nonlinear regression model showed that time management predicted 6.6% of academic stress (β=0.430; p<0.001), 9.2% of social support (β= 0.430; p<0.001) and 11.5% of academic achievement (β= 0.430; p<0.001). Conclusions: Time management is important in all stages of the educational process; it is essential the support of parents and/or guardians to teach tools for the organization and prioritization of academic activities in order to increase terminal efficiency and success in the study.